Aleurodicus talamancensis, a new whitefly species damaging plantation bananas in Costa Rica, with discussion of a montane orchid-feeding population (Sternorrhyncha, Aleyrodidae) - Martin, Jon H. (Zootaxa, 2005)
A new species of Aleurodicus Douglas is described from Costa Rica. It is a serious pest of plantation bananas in low-altitude areas of Limón Province. A single population from an orchid plant in high altitude montane forest differs in several respects, but is thought to be conspecific and is discussed in detail. This new species is discussed in relation to two similar species which together form the distinctive A. niveus Martin species-group.